Raman characterization of orientation in poly(lactic acid) films - Smith, Patrick B.; Leugers, Anne; Kang, Shuhui; Yang, Xiaozheng; Ling Hsu, Shaw (Macromolecular symposia., 2001)
Poly(lactic acid) is a new biopolymer material which is marketed by Cargill Dow Polymers under the tradename Nature Works*. One major application for this material is biaxially oriented films for food packaging because it possesses excellent barrier for flavor constituents, deadfold and heat sealability. Shrinkage must be minimized when the film is heat sealed for these applications and, therefore, characterization of the orientation of the amorphous phase of PLA films is necessary. Raman spectroscopy methodology has been developed to quantify orientation in PLA films. Bands were assigned to crystalline and amorphous phases of PLA such that orientation in both phases could be monitored. Raman depolarization ratios were used to characterize uniaxial systems but were insufficient for most biaxial draws. A new phenomenon for oriented films involving Raman band shifts was observed in these systems, and was shown to be capable of determining orientation, even for symmetrical biaxially drawn films. The origin of these shifts, as well as their use for the quantification of orientation will be discussed. Further, since the line widths of the bands could be used to quantify crystallinity, both crystallinity and orientation could be determined with one measurement.